Does Audio Drama Improve Knowledge and Practice Regarding Personal Hygiene Among Visually Impaired Children: Life Sciences-Nursing - Chocka Lingam, Geetha (International Journal of Life Science and Pharma Research, 2023)
Personal hygiene includes brushing, bathing, hand hygiene, and adequate sleep. Personal hygiene health promotion practices are frequently like general health promotion practices. Brushing, bathing, hand hygiene, and getting enough sleep are all examples of specific health promotion related to good personal hygiene. However, children who are blind or visually impaired children are more likely to contract an infection due to poor personal hygiene. The objectives were to assess the Knowledge and Practice regarding Personal hygiene among visually impaired children. To evaluate the effectiveness of Audio drama on knowledge regarding Personal hygiene. To associate the Knowledge and Practice regarding Personal hygiene with a selected demographic variable of visually impaired children. The study employed a pre-experimental research design. The research was carried out at Cuddalore’s Government Blind School. Visually impaired children 30 numbers were included in the study. The sample was chosen using a simple random sampling technique. A structured interview questionnaire and checklist were used to assess the knowledge and practice of visually impaired children for data collection. The audio drama covers the introduction to personal hygiene, problems caused by poor personal hygiene practices, and proper personal hygiene practices. After seven days, a posttest was conducted. According to the findings, 21 (70%) of visually impaired children had insufficient knowledge in the pretest, but all 30 (100%) of visually impaired children had adequate knowledge in the posttest. In terms of percentage of practice, 14 (46%) of visually impaired children had fair practice in the pretest, and all 30 (100%) had good practice in the posttest. 2. The p-value was highly significant at p >0.001 level for the effectiveness of audio drama on knowledge and practice of personal hygiene between the pretest and posttest. It implied that audio drama was effective for visually impaired children. To conclude, the findings suggest that audio drama can help visually impaired children improve their knowledge and practice of personal hygiene.